Concomitant effects of multiple disturbances (logging, fire, biological invasion) on native tree abundances into West Africa's semi-deciduous forests - (:unkn) unknown (My University, 2023)
West African semi-deciduous forests face multiple disturbances directly linked to human activities. A major unknown is the concomitant effects that these disturbances might have on forest communities. We (i) studied the long-term (>30 years) response of 17,038 trees from 207 semi-deciduous forest species to the three disturbances (fire, logging and biological invasion) in a 100-ha experimental set-up, (ii) examined the links between species-specific responses and functional traits related to resource acquisition and to defense strategies, and (iii) listed species vulnerable to local disturbances, in relation to their global vulnerabilities. Our results show that all three disturbances have long-lasting negative impacts on the current abundance of species. The most sensitive species to disturbance are those with a conservative resource strategy and which invest little in defensive strategies. We found that species that are locally vulnerable to fire are also globally highly threatened species. In the context of West Africa's almost extinct forests, we propose (i) the conservation of the last remaining deciduous forests in West Africa, knowing that opening them to logging simultaneously increases the risk of fire, (ii) the use of native species in reforestation programs to limit the risk of biological invasions, and (iii) the implementation of fire control strategies in conservation and forest restoration policies.
Keywords: African Research